A Platform for Co-Culture of Primary Human Colonic Epithelium With Anaerobic Probiotic Bacteria - Kim, Raehyun; Wang, Yuli; Sims, Christopher E.; Allbritton, Nancy L. (Frontiers in Bioengineering and Biotechnology, 2022)
An in vitro platform was designed and optimized for the co-culture of probiotic anaerobic bacteria with a primary human colonic epithelium having a goal of assessing the anti-inflammatory impact of the probiotic bacteria. The device maintained a luminal O2 concentration at <1% while also supporting an oxygenated basal compartment at 10% for at least 72 hours. Measurement of the transepithelial resistance of a confluent colonic epithelium showed high monolayer integrity while fluorescence assays demonstrated that the monolayer was comprised primarily of goblet cells and colonocytes, the two major differentiated cell subtypes of the colonic epithelium. High monolayer barrier function and viability were maintained during co-culture of the epithelium with the probiotic obligate anaerobe Anaerobutyricum hallii (A. hallii). Importantly the device supported a static co-culture of microbes and colonic epithelium mimicking the largely static or low flow conditions within the colonic lumen. A model inflamed colonic epithelium with high interleukin-8 (IL-8) secretion was generated by addition of tumor necrosis factor- (TNF-) and lipopolysaccharide (LPS) to the basal and luminal epithelium sides, respectively. Co-culture of A. hallii with the inflamed intestine diminished IL-8 secretion by >40% which could be mimicked by co-culture with the A. hallii metabolite butyrate. In contrast, co-culture of the inflamed epithelium with two strains of lactic acid-producing bacteria, Lactobacillus rhamnosus GG (LGG) and Bifidobacterium adolescentis (B. adolescentis), did not diminish epithelial IL-8 secretion. Co-culture with colonic epithelial cells from different donors demonstrated a consistent anti-inflammatory effect by A. hallii, but distinct responses to co-culture with LGG and B. adolescentis. The demonstrated system offers a simple and easily adopted platform for examining the physiologic impact of alterations in the intestinal epithelium that occur in the presence of probiotic bacteria and their metabolites.